Price-effectiveness: Pharmacoeconomics, value and the right price for HPV vaccines (2016)
Drawing on a pragmatist approach to pricing, this article discusses the impact of cost-effectiveness analysis (CEA) in the pricing strategies of pharmaceutical companies. Through an analysis of the human papillomavirus (HPV) vaccination, this article illustrates the strategic appropriation of evidence-based medicine (narratives and practices) that pharmaceutical companies have undertaken to enhance the value of their products. While governments are concentrated on the measurement of costs and efficiency (cost-effectiveness), companies attempt to find the threshold of effectiveness that supports their estimation of value. I have called such mode of calculation, price-effectiveness. Pharmaceutical companies engage in different ways with CEA in devising their own price strategies. First, CEA is used as an instrument to raise HPV vaccines as a matter of interest for health authorities. Second, companies produce models to maximise the effectiveness of their products. Third, the expense side of CEA has opened an opportunity to represent some conditions as diseases in order to increase the potential value of the vaccine, expressed in a higher price. Debates and practices of pricing offer a unique opportunity to trace how particular forms of quantification have become the common ground in the demonstration of value in healthcare and the adaptation of companies.